Turritellidae (Gastropoda) of the Miocene Paratethys Sea with considerations about turritellid genera - Harzhauser, Mathias; Landau, Bernard (Zootaxa, 2019)
We present a critical evaluation of the taxonomy, stratigraphy and biogeography of the turritellid gastropods of the Miocene Paratethys Sea. 159 species-level names and 6 infrasubspecific names have been used for Paratethyan Turritellidae since 1848. Of these, only 35 species are accepted herein as valid species, with some uncertainties due to poor preservation or limited access to type material. Maximum diversities occurred during the early middle Miocene (Langhian, Badenian) coinciding with the Miocene Climatic Optimum. Whilst early Miocene turritellid assemblages are characterized by large to very large species of Peyrotia, Turritella and Allmonia, middle Miocene assemblages are predominated by medium-sized species of Archimediella, Helminthia, Oligodia and Ptychidia. The taxonomic composition of these faunas, with representatives of Archimediella, Helminthia, Mesalia and Vermicularia suggests a biogeographic affiliation with Atlantic and especially West African faunas.                Turritellinella new gen. is established as new genus for the eastern Atlantic-Mediterranean Turritella tricarinata/communis complex. Viennella is described as new genus with Turritella incisaeformis Csepreghy-Meznerics 1956 as type species. Allmonia new gen. is introduced as new genus for European Cenozoic Protominae previously placed in Protoma. For the first time, inner lirae are documented as conchological features of Turritellidae.                Six species are described as new, three within the Turritellinae: Archimediella carpathica new sp., Ptychidia erynella new sp. and Viennella ignorata new sp., and three within the Pareorinae: Mesalia sovisi new sp., Mesalia stryriaca new sp. and Mesalia bohnhavasae new sp.. Ptychidia austrorotundata new nom. is proposed as new name Turritella turris rotundata Schaffer 1912, non Turritella rotundata Grzybowski 1899. We designate lectotypes for Turritella gradata Menke in Hörnes, 1855, Haustator striatellatus Sacco, 1895, Allmonia carniolica (Stache, 1858) and Allmonia alterniplicata (Sacco, 1895). Neotypes are designated for Archimediella abundans (Handmann, 1882), Archimediella hoernesi (Rolle, 1856), Ptychidia partschi (Rolle, 1856), Ptychidia? ernesti (Handmann, 1882). Rhabdosis Townes, 1970 (Hymenoptera, Ichneumonidae) is a junior homonym of Rhabdosis Handmann 1882 (Gastropoda, Turritellidae) and will need a new name.